Pengertian Art Direction dan Peranan Seorang Art Director dalam Periklanan - Bimo, Aryo (Humaniora, 2010)
Nowadays advertising is a field that is progressing rapidly and is quite popular majors marked by numerous educational institutions both private and the country that opened specialization advertising. One of the positions in the field of advertising that quite popular is Art Director. The skill of art directing is a bit much has been represented in the department of Visual Communication Design or Graphic design. But it is sometimes still confused between the duties and role of an art director and a graphic designer. This article gives a general overview of what is meant by Art Director as well as roles and duties.